The Impact of Students` Needs and Interests on Vocabulary Acquisition in a Private University in Georgia (A Case of Georgian Higher Education Institution) - Mshvidobadze, Tamta; Pipia, Ekaterine (European Scientific Journal, ESJ, 2021)
The aim of this research was to measure the impact of students` interest-based materials on vocabulary skills development through a twotailed quasi-experiment. Contemporary classrooms with digital natives seeking 21st-century skills require many significant changes in the instructional process. Being put in a democratic, student-centered environment, students have to be granted the opportunity to personalize their learning process. The issue of adjusting and tailoring materials to learners` needs, demands, and interests is widely considered daunting for teachers all over the world. The presented article highlights the importance of designing contextualized materials and adjusting materials to learners` interests and needs to achieve desired learning outcomes. The statistical data were gathered using a two-tailed quasi-experimental design in two control and two experimental groups through pre, while, and post-tests, and analyzed by paired samples tests. The study revealed that vocabulary acquisition is influenced significantly when materials are designed according to students` interests and needs.